Agricultural Transformation and Market Integration (ATMI) in ASEAN countries: Responding to food security and inclusiveness concerns - International Food Policy Research Institute; Southeast Asian Regional Center for Graduate Study and Research in Agriculture (International Food Policy Research Institute, 2021)
Structural transformation in Southeast Asia poses challenges to the regions' food security and inclusive agricultural growth agenda. Integration of agricultural markets within ASEAN is high on the agenda given the current pressure on moving towards the establishment of a common market. An improvement in agricultural value chains' competitiveness is supportive of the broader effort towards achieving ASEAN economies that are competitive. Southeast Asia faces two fundamental challenges: First, regional supply chains of key crops are proliferating and primary producing countries fear losing sovereignty and missing opportunities for domestic industrialization and value addition. Second, national and rural food-security strategies are often at odds with farm diversification away from traditional staple crops. Furthermore, with a growing urban population food price shocks are perceived as a major threat by all countries in the region, leading to sub-optimal outcomes for each country as well as collectively.